EXCAVATION OF THE BURIAL MOUNDS ON THE LEFT BANK OF THE PSENAFA RIVER NEAR MAYKOP - Bakusev, Marat Arturovic (History, Archeology and Ethnography of the Caucasus, 2023)
In 2019 and 2020, 5 km north of the city of Maykop in the Republic of Adygea, security and rescue excavations of mounds were carried out in connection with the construction of a highway bypassing the city of Maykop. Seven burial mounds were investigated, six of which were located compactly as part of the burial mound on the low, left bank of the upper Psenafa River, and one mound was located 1.5 km from the burial mound, but culturally and chronologically related to the studied mounds. During the work in three mounds, stone structures were identified under the mounds, which may represent ritual stone platforms used for memorial purposes. The ceramic fragments found here also made it possible to date this group of monuments. Four mounds contained burials, which made it possible to conduct a sex and age analysis, and the findings obtained – to date these burials. Based on the results of the work, it was concluded that the kurgan field was used twice – by the tribes of the Maykop-Novosvobodnenskaya community and the Meots. The purpose of the article is to introduce into scientific circulation the materials obtained in the course of the work, a preliminary analysis of the findings and interpretation of the buried structures.
Keywords: burial mound; Maykop-Novosvobodnenskaya community; meots; funeral rite; ritual site